Recruiting warriors or guardians?: a content analysis of police recruitment videos - Koslicki, Wendy M. (Policing and society, 2021)
United States police response to the 2014 Ferguson riots has directed scholarly and public attention towards police militarisation, renewing interest in community policing strategies as a potential strategy to decrease militarised policing. However, these concepts are vague and require further empirical examination. This article proposes a novel method of empirically studying militarisation and community policing by using police recruitment videos, which act as advertisements of departments’ self-depictions. Themes of militarisation and community-oriented policing are observed using a quantitative content analysis of videos collected from the 200 largest United States policing agencies. Community-oriented themes are found to occur across a higher percentage of the sample than militarised themes, and for longer average durations of time. However, there is some complexity present across the variables, and subsets of the videos fall into the extreme ends of the two concepts. This exploratory study acts as a foundation for examining future research questions regarding police culture and behaviour, viewer semiotics, and police administrator recruiting recommendations.